Principal’s Leadership In Developing The Competencies Of Physical Education Teachers In Muhammadiyah Nitikan Elementary School Yogyakarta - Arifin Arifin; Enung Hasanah (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This study explores the principal's leadership role in developing Muhammadiyah Nitikan Yogyakarta Elementary School's physical education teacher's competencies. The researchers used a qualitative method in the research. The researchers collected the data through collecting data from observations, interviews, and documentation. The sample is determined through purposive sampling. The number of participants in this study amounted to 10 respondents. The sample consisted of principals, curriculum time, arts and talent lecturers, physical education teachers, and students. This study concluded that the principal had made full efforts by enforcing programs and activities to develop physical education (PE) teachers' competencies at Muhammadiyah Nitikan Yogyakarta Elementary School to teach physical education effectively and master learning materials. Programs enforced to improve the competencies of physical education teachers namely as follows: 1) planning for developing the competence of PE teachers by following the Teacher Work Group (KKG) and the Subject Teacher Deliberation (MGMP); 2) Mapping the competence of teacher skills through competency tests and writing scientific articles or enforcing classroom action research (PTK); 3) Giving opportunities for PE teachers to attend sports training and seminars; 4) Direct coaching by the principal.